Dental Students' Intent to Practice in Rural Communities Before and After Community‐Based Rotations in a Rural Area. Issue 11 (1st November 2019) - Mays, Keith A.; Scheffert, Donna Rae; Maguire, Meghan; Lunos, Scott; Johnson, Renee; Jackson, Linda; Riggs, Sheila
Abstract : Community‐based dental education (CBDE) has the potential to positively impact the educational process in a manner that both contributes to educational outcomes and shapes the learner's behavior. The aim of this study was to determine the correlation between dental students' intended practice location and the size of their hometown and to assess any impact their CBDE rotation in a rural location had on practice location intention. From March 7, 2016, to August 12, 2018, fourth‐year students at one U.S. dental school were invited to complete a ten‐item questionnaire prior to and after their four‐week clinical rotations at a rural clinic. Of the 123 dental students on rotation at the clinic during this time, 106 completed the pre‐rotation survey and 112 the post‐rotation survey, for response rates of 86% and 91%, respectively. Prior to the rotation, 58.6% selected one of the rural locations as an ideal practice location, and that percentage increased slightly to 61.4% after the rotation; the difference was not statistically significant (p=0.984). The results did show a significant increase from pre to post rotation for women intending to practice in rural communities (p=0.0413). This study found that students' intent to practice in a rural location was not significantly affected by a clinical rotation in a rural clinic; however, there was strong evidence that students from rural communities intended to practice in rural communities after graduation.